Analisis Kualitas Sistem Knowledge Management Metode Quality Function Deployment (Studi kasus:PT.Pupuk Sriwidjaja Palembang) - Sari, Yolita Lara; Santi, Rusmala; Jaya, Irfan Dwi (MATICS, 2020)
Knowledge management system is a system used by permanent employees of PT.Pupuk Sriwidjaja Palembang which aims to accommodate all the knowledge or work experience known to all employees at PT. Sriwidjaja Palembang Fertilizer. In this study there are some problems such as material shared by the admin such as videos, modules and other material that cannot be downloaded by users or users, there is no menu to connect to admin or system users, when the user or user shares learning material or work experience there is no notification directly to the system whether rejected or approved by the admin, there is no menu that can help beginners who are first using the knowledge management system. The purpose of this research is to analyze the quality level of knowledge management system services and how to improve the quality of knowledge management system services by utilizing the Quality Function Deployment method. to identify by distributing to respondents who were processed using Quality Function Deployment (QFD). The results of the distribution of questionnaires get a value of 3,764 with a low category which means it needs to be improved and processing in the QFD method in the House of Quality matrix there are 16 technical responses as a solution to improve service quality. Priority determination is obtained from calculating the relationship between user desires and technical responses then used to determine the priority of improvements that will be applied first.